Revisionings of Hamlet: the crux of an interpretive paradigm - Mohammad Safaei,; Ruzy Suliza Hashim, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
This article is a brief survey of Hamlet criticism along with different types of revisioning Hamlet in a variety of genres since the early twentieth century. Four major types of revisioning Hamlet are considered in this article: absorption of Hamlet by a competent writer as a challenge to Shakespeare; rewriting of the play as a response to the questions unaddressed in the original text; revisioning of the play as a feminist struggle intent upon defending women against patriarchal readings of them; transforming Hamlet as a postcolonial urge to rewrite the past. Further, it is argued that varied types of revisioning, adapting, or transforming Hamlet, though roughly different in their exact significations and delineations, are the consequence of two major factors: psychological reaction to Shakespeare, and, being situated within a socio-political context. By reducing the causes of revisioning into the two broad categories of psychological and contextual, varied types of revisioning that are ostensibly discrepant and unrelated may obtain a common foundation for analysis and comparison. Further, it is argued that Hamlet is surrounded by the enormous bulk of criticism on Hamlet which informs the readers and affects their interpretation of both the play and its revisionings. Developing an interpretive paradigm for revisioning phenomenon entails the investigation of the basic concepts on which revisioning phenomenon is founded. Revisionism is a complex phenomenon; a reductionist approach toward the basic concepts involved in revisioning and its analysis can be regarded as a step toward gaining more insight into the revisioning phenomenon in our era.